ROS signaling by NADPH oxidase 5 modulates the proliferation and survival of prostate carcinoma cells. Issue 1 (5th January 2015) - Höll, Monika; Koziel, Rafal; Schäfer, Georg; Pircher, Haymo; Pauck, Alexander; Hermann, Martin; Klocker, Helmut; Jansen‐Dürr, Pidder; Sampson, Natalie
Abstract : Prostate cancer (PCa) is the most commonly diagnosed cancer and second leading cause of male cancer death in Western nations. Thus, new treatment modalities are urgently needed. Elevated production of reactive oxygen species (ROS) by NADPH oxidase (Nox) enzymes is implicated in tumorigenesis of the prostate and other tissues. However, the identity of the Nox enzyme(s) involved in prostate carcinogenesis remains largely unknown. Analysis of radical prostatectomy tissue samples and benign and malignant prostate epithelial cell lines identified Nox5 as an abundantly expressed Nox isoform. Consistently, immunohistochemical staining of a human PCa tissue microarray revealed distinct Nox5 expression in epithelial cells of benign and malignant prostatic glands. shRNA‐mediated knockdown of Nox5 impaired proliferation of Nox5‐expressing (PC‐3, LNCaP) but not Nox5‐negative (DU145) PCa cell lines. Similar effects were observed upon ROS ablation via the antioxidant N‐acetylcysteine confirming ROS as the mediators. In addition, Nox5 silencing increased apoptosis of PC‐3 cells. Concomitantly, protein kinase C zeta (PKCζ) protein levels and c‐Jun N‐terminal kinase (JNK) phosphorylation were reduced. Moreover, the effect of Nox5 knockdown on PC‐3 cell proliferation could be mimicked by pharmacological inhibition of JNK. Collectively, these data indicate that Nox5 is expressed at functionally relevant levels in the human prostate and clinical PCa. Moreover, findings herein suggest that Nox5‐derived ROS and subsequent depletion of PKCζ and JNK inactivation play a critical role in modulating intracellular signaling cascades involved in the proliferation and survival of PCa cells. © 2014 The Authors. Molecular Carcinogenesis published by Wiley Periodicals, Inc.